Fitri IMPLEMENTASI MEDIA VIDEO DALAM PEMBELAJARAN AKHLAK DI KELAS I WUSTHO MADIN BAYT AL-HIKMAH - Fitri Kurnia (Tarbawi : Jurnal Studi Pendidikan Islami, 2024)
Research on the implementation of video-based learning media in Class 1 Wustho Madin Pondok Pesantren Bayt Al-Hikmah was conducted in response to various problems encountered in the field of learning practices. One of the problems faced is the conventional learning system, where lecture methods dominate the delivery of subject matter. As a result, students tend to feel bored and less interested during lessons, and the classroom atmosphere is lacking. This research aims to determine: 1) The implementation of video-based learning media in moral education in Class 1 Wustho Madrasah Diniyah Bayt Al-Hikmah. 2) Supporting and inhibiting factors in the implementation of video-based learning media in moral education in Class 1 Wustho Madrasah Diniyah Bayt Al-Hikmah. The method used in this research is a qualitative case study method by exploring the phenomenon of implementing video-based learning media in moral education in Class 1 Wustho Madrasah Diniyah Bayt Al-Hikmah. Data collection techniques used are Observation, Interviews, and Documentation. The results of this study indicate that 1) The implementation of video-based learning media in moral education subjects in the madin program class 1 wustho at PP Bayt Al-Hikmah Kota Pasuruan has been continuously applied in every learning process. The use of media supports the learning process through several applications and learning sources. Laptops as the main supporting tool and video-based learning as a form of contribution to learning media applied in teaching and learning activities directly in the madin program class 1 wustho at PP Bayt Al-Hikmah Kota Pasuruan. 2) However, there are also several inhibitors, namely network connections, applications in video-based learning, and laptops often experience troubles in terms of active and interactive costs.